2010
DOI: 10.1097/mcp.0b013e32833ab0b6
|View full text |Cite
|
Sign up to set email alerts
|

Initial evaluation of the nonsmall cell lung cancer patient: diagnosis and staging

Abstract: Integrating new technologies such as PET-CT and endobronchial ultrasound into the initial evaluation of patients can save unnecessary diagnostic procedures and lead to more rapid and accurate staging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 41 publications
1
25
0
Order By: Relevance
“…If EBUS-TBNA and bronchoscopy failed to provide a specifi c infi ltration of the mediastinum, the 2007 American College of Chest Physicians evidence-based guidelines recommend mediastinal lymph node sampling as the fi rst procedure, since this can both diagnose and stage disease with one procedure. 2,[4][5][6] This is consistent with other guidelines on lung cancer that recommend think ing carefully before performing a test that gives only a diagnosis when information on staging is also needed. [7][8][9] However, there may be large gaps between what is recommended in guidelines and what is actually done in practice.…”
Section: Methodssupporting
confidence: 70%
“…If EBUS-TBNA and bronchoscopy failed to provide a specifi c infi ltration of the mediastinum, the 2007 American College of Chest Physicians evidence-based guidelines recommend mediastinal lymph node sampling as the fi rst procedure, since this can both diagnose and stage disease with one procedure. 2,[4][5][6] This is consistent with other guidelines on lung cancer that recommend think ing carefully before performing a test that gives only a diagnosis when information on staging is also needed. [7][8][9] However, there may be large gaps between what is recommended in guidelines and what is actually done in practice.…”
Section: Methodssupporting
confidence: 70%
“…CT and PET imaging, although useful, do not always have suffi cient positive and negative predictive value to guide treatment decisions in these cases. 2,4,11 The result of relying solely on imaging to stage the mediastinum is that some patients will be falsely up-staged, leading to missed opportunities for surgery and possibly cure. Conversely, other patients will be falsely under-staged, leading to unnecessary thoracotomies and complications.…”
mentioning
confidence: 99%
“…All with suspected lung cancer with mediastinal adenopathy without distant metastases because the procedure can be used for both diagnosis and staging. [2][3][4][11][12][13][14][15][16] However, to our knowledge, only one single-center comparative effectiveness study has evaluated how test sequencing affects outcomes. 17 The goal of the present study was to compare practice patterns and outcomes of diagnostic and staging strategies in patients with lung cancer with mediastinal lymph node involvement without distant metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, multiple guidelines recommend biopsy of the mediastinal lymph nodes fi rst in patients with evidence of nodal disease rather than biopsy of the peripheral mass. [2][3][4][11][12][13][14][15][16] A previous single-center retrospective study suggested that a strategy of sampling the mediastinum fi rst resulted in fewer tests and complications than a as the fi rst test, those with stage II disease were more likely to have mediastinal sampling than those with stage IIIA or IIIB disease (67% vs 34% vs 16%, respectively; P , .001).…”
Section: Number Of Invasive Tests Performedmentioning
confidence: 99%
See 1 more Smart Citation